Increase in Beta-Band Activity during Preparation for Overt Speech in Patients with Parkinson’s Disease - Sörös, Peter; Doñamayor, Nuria; Wittke, Catharina; Al-Khaled, Mohamed; Brüggemann, Norbert; Münte, Thomas F. (Frontiers in Human Neuroscience, 2017)
Speech impairment is a frequent and often serious symptom of Parkinson's disease (PD), characterized by a disorder of phonation, articulation and prosody. While research on the pathogenesis of the prominent limb motor symptoms has made considerable progress in recent years, the pathophysiology of PD speech impairment is still incompletely understood. To investigate the neural correlates of speech production in PD, EEG was recorded in 14 non-demented patients with idiopathic PD and preserved verbal fluency on regular dopaminergic medication (8 women; mean age ± SD: 69.5 ± 8.0 years). The control group consisted of 15 healthy age-matched individuals (7 women; age: 69.7 ± 7.0 years). All participants performed a visually-cued, overt speech production task; required utterances were papapa and pataka. During the preparatory phase of speech production, in a time window of 200-400 ms after presentation of the visual cue, β-power was significantly increased in PD patients compared to healthy controls. Previous research has shown that the physiological decrease of β-power preceding limb movement onset is delayed and smaller in PD patients off medication and normalizes under dopaminergic treatment. By contrast, our study demonstrates that β-power during preparation for speech production is higher in patients on dopaminergic therapy than controls. Thus, our results suggest that the mechanisms that regulate β-activity preceding limb movement and speech production differ in PD. The pathophysiological role of this increase in β-power during speech preparation needs to be determined.